Determinants of gold nanoparticle interactions with Proteins: Off-Target effect study - Ghalandari, Behafarid; Asadollahi, Kazem; Ghorbani, Farnaz; Ghalehbaghi, Suzan; Rafiee, Saharnaz; Komeili, Ali; Kamrava, Seyed Kamran (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2022)
Photothermal therapy is one of the promising approaches toward cancer treatment. To date, several compounds have been developed for this application, among which nanoparticles are attracting ever-increasing attention. One of the obstacles in developing efficient photothermal nanoparticle agents is their off-target effect which is mainly mediated via non-specific interactions with proteins. Such interaction not only reduces the bioavailability of the agent but also will cause protein aggregation that can be lethal. So, gaining knowledge on the mechanisms mediating such interactions will facilitate development of more effective agents. Our last studies showed the mechanism of action of two modified gold nanoparticles, folic acid functionalized gold nanoparticles (FA-AuNPs) and gold shelled Fe(3)O(4 )nanoparticles (AuFeNPs), as photothermal agents. In the current work, we focus on the interaction of these two NPs with human serum albumin (HSA) and human hemoglobin (Hb) as model proteins. The complex formation between NPs and proteins was investigated by fluorescence spectroscopy, dynamic light scattering and circular dichroism. Our data distinguishes the very distinct mode of interaction of charged and neutral NPs with proteins. While the interaction of neutral AuFeNP to proteins is protein dependent, charged nanoparticles FA-AuNP interact indistinguishably with all proteins via electrostatic interactions. Moreover, complexes obtained from FA-AuNPs with proteins are more stable than that of AuFeNP. However, the secondary structure content of proteins in the presence of NPs indicates the insignificant effect of NPs on the secondary structure of these proteins. Our data propose that the charge functional-ization of the NPs is an effective way for modulating the interaction of nanoparticles with proteins. (C) 2021 Published by Elsevier B.V.
CRIS-Team WoS Importer:2022-03-11